Empowering Female Entrepreneurship Through Pesantren: a Strategic Model for Economic Empowerment - Fauzan Husaini (EKONOMIKA SYARIAH : Journal of Economic Studies, 2025)
Indonesian Islamic Boarding School (Pesantren) presents significant opportunities for the economic empowerment of the Muslim community. This study aims to examine how the pesantren environment influences the entrepreneurial intentions of female students (santriwati). Employing Structural Equation Modelling Partial Least Squares (SEM-PLS) along with the Higher Construct Model (HCM) approach, the study analyzes data collected through questionnaires distributed to santriwati at Pesantren Idrisiyyah in Tasikmalaya. The findings reveal that the presence and activities of pesantren positively influence the entrepreneurial intentions of santriwati, encouraging them to engage in business initiatives. Furthermore, the study highlights that pesantren-based programs designed to nurture entrepreneurial character significantly enhance key competencies, including self-efficacy, risk-taking, planning, leadership, persistence, and social skills. These competencies are crucial for fostering an entrepreneurial mindset and preparing students for future business endeavors. The study offers valuable insights for the development of strategic frameworks to strengthen pesantren programs focused on entrepreneurship. By integrating character building with practical business exposure, pesantren can play a vital role in shaping a generation of economically empowered and socially responsible Muslim entrepreneurs. Pondok pesantren di Indonesia telah menghadirkan peluang yang signifikan bagi pemberdayaan ekonomi umat Islam. Penelitian ini berupaya untuk meneliti bagaimana pesantren memengaruhi minat berwirausaha santriwati. Penelitian ini menggunakan Structural Equation Modelling Partial Least Squares (SEM-PLS) bersama dengan pendekatan Higher Construct Model (HCM) untuk analisis data. Data untuk penelitian ini dikumpulkan melalui kuesioner yang diberikan kepada santriwati di Pesantren Idrisiyyah di Tasikmalaya. Temuan penelitian ini menunjukkan bahwa keberadaan pesantren berdampak positif pada minat santriwati untuk terlibat dalam kegiatan bisnis. Penelitian ini juga mengungkapkan bahwa program-program di dalam Pesantren yang bertujuan untuk menumbuhkan karakter wirausaha dapat meningkatkan kompetensi seperti efikasi diri, pengambilan risiko, perencanaan, kepemimpinan, kegigihan, dan kemampuan bersosialisasi. Temuan penelitian ini dapat menjadi landasan yang berharga untuk mengembangkan kerangka strategis bagi program-program pesantren yang bertujuan untuk menumbuhkan kewirausahaan di kalangan santri